Penentuan Jumlah Persediaan Sparepart Berdasarkan Waktu Maintennance Headtruck Giga di PT. Bima Site Berlian - Setiawan, Febri Hari; Wati, Putu Eka Dewi Karunia (Jurnal Teknik Industri Terintegrasi (JUTIN), 2024)
PT. Berkah Industri Mesin Angkat (PT.BIMA) is a company engaged in the maintenance and supply of port equipment. In the service process there are five types of transport aircraft at PT BIMA. Loading and unloading equipment operates continuously, causing a decrease in the level of equipment reliability and causing frequent breakdowns and high downtime on the machines, especially the Headtruck equipment. To minimize breakdowns and downtime, it is necessary to have a good maintenance scheduling system to prevent machine damage. Mean Time to Failure (MTTF) is one of the company's provisions as a reference for determining an effective maintenance schedule. Therefore, appropriate corrective action is needed to ensure the number of spare parts available so that equipment downtime is not too long which results in decreased/unstable levels of availability and reliability.